Using multi-criteria decision making to highlight stakeholders’ values in the corridor planning process - Bethany Stich; Joseph H. Holland; Rodrigo A. A. Nobrega; Charles G. O'Hara (Journal of Transport and Land Use)
The processes for environmental review and public participation mandated by the National Environmental Policy Act (NEPA) and the 2005 Safe, Accountable, Flexible, Efficient Transportation Equity Act - A Legacy for Users (SAFETEA-LU), have become overly time-consuming and costly in transportation planning. This paper focuses on the implementation of transportation policy, highlighting how its complex nature challenges the traditional policy process theories. Federal and local perspectives are used as a basis for top-down and bottom-up implementation models. In addition, the authors discuss the conflicting nature of transportation policy implementation within decision processing and suggest an implementation tool that can aid transportation and planning professionals. The authors suggest that the use and integration of existing data from geospatial technologies and economic modeling can result in a visual Multiple Criteria Decision Making (MCDM) model that can aid in streamlining and enhancing the NEPA process, agency coordination, and public participation in different administration levels.